2012
DOI: 10.1016/j.neuroimage.2011.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of smoking cue reactivity: A meta-analysis of fMRI studies

Abstract: Reactivity to smoking-related cues may be an important factor that precipitates relapse in smokers who are trying to quit. The neurobiology of smoking cue reactivity has been investigated in several fMRI studies. We combined the results of these studies using activation likelihood estimation, a meta-analytic technique for fMRI data. Results of the meta-analysis indicated that smoking cues reliably evoke larger fMRI responses than neutral cues in the extended visual system, precuneus, posterior cingulate gyrus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
343
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(377 citation statements)
references
References 94 publications
33
343
1
Order By: Relevance
“…These latter regions primarily rely on dopamine, GABA, opioid, and glutamate signaling and are implicated in the development of incentive salience (Kalivas and Volkow, 2005). Further, we found that greater tonic subjective methamphetamine craving was associated with greater activation of the precuneus, a region highlighted by multiple meta-analyses to be reliably involved in cue-reactivity for various substances of abuse (Engelmann et al, 2012;Schacht et al, 2013a). Taken together, these results suggest that this novel paradigm is an effective probe of methamphetamine cueinduced craving in individuals with methamphetamine use disorders.…”
Section: Bold Measures Of Methamphetamine Cue-reactivitymentioning
confidence: 58%
See 2 more Smart Citations
“…These latter regions primarily rely on dopamine, GABA, opioid, and glutamate signaling and are implicated in the development of incentive salience (Kalivas and Volkow, 2005). Further, we found that greater tonic subjective methamphetamine craving was associated with greater activation of the precuneus, a region highlighted by multiple meta-analyses to be reliably involved in cue-reactivity for various substances of abuse (Engelmann et al, 2012;Schacht et al, 2013a). Taken together, these results suggest that this novel paradigm is an effective probe of methamphetamine cueinduced craving in individuals with methamphetamine use disorders.…”
Section: Bold Measures Of Methamphetamine Cue-reactivitymentioning
confidence: 58%
“…The increases in self-reported, subjective methamphetamine craving during the presentation of methamphetamine as compared to control cues highlight the initial efficacy of the task in eliciting cue-induced craving. The primary BOLD results depicted greater methamphetamine (vs control) cue-elicited activation in regions that are commonly seen to be cue-reactive for other substances in dependent populations (eg, middle frontal gyrus, ACC, posterior cingulate cortex (PCC)/precuneus, thalamus, insula, inferior occipital cortex, and brain stem) (Engelmann et al, 2012;Schacht et al, 2013a), and in commonly described 'reward'-or 'reinforcement'-related regions (eg, left ventral striatum (NAcc), bilateral dorsal striatum (caudate, putamen), VTA, hippocampus, and amygdala). These latter regions primarily rely on dopamine, GABA, opioid, and glutamate signaling and are implicated in the development of incentive salience (Kalivas and Volkow, 2005).…”
Section: Bold Measures Of Methamphetamine Cue-reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The medial orbitofrontal cortex and supplementary motor area were particularly implicated as being more segregated. Indeed, AD individuals have reduced volume and cortical thickness of the orbitofrontal cortex (Durazzo et al 2011) that predicts future relapse (Beck et al 2012) and simultaneously show heightened drug cue reactivity in this region (Chase et al 2011; Kuhn & Gallinat 2011; Engelmann et al 2012), which is modulated by gene type during naltrexone (OPRM1 gene G allele carriers) (Kareken et al 2010). Similarly, supplementary motor area volume is reduced in binge drinkers (Kvamme et al 2016), and AD subjects show increased SMA activity related to impulsivity (Claus, Kiehl, & Hutchison 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral aHPC and pHPC ROIs were defined following a prior study of aHPC and pHPC connectivity (Chen and Etkin, 2013), taking the anterior-most third and posterior-most third of an HPC ROI consisting of voxels with a 460% likelihood of being in HPC (as defined by the Harvard-Oxford probabilistic structural axis). The following additional ROIs, chosen a priori based on preclinical research (Bossert et al, 2011;Fuchs et al, 2005;McLaughlin and See, 2003;Otis et al, 2014), our previous neuroimaging studies (McClernon et al, 2005(McClernon et al, , 2007(McClernon et al, , 2009) and metaanalysis (Engelmann et al, 2012;Kuhn and Gallinat, 2011;Tang et al, 2012) of cue-reactivity, were created in PickAtlas (Maldjian et al, 2003): (1) ventral striatum (5 mm radius sphere centered on ± 6,4, − 5); (2) amygdala (anatomical); (3) insula (5 mm radius sphere centered on ± 38,10,6); (4) mPFC inclusive of portions of rostral anterior cingulate cortex (5 × 10 × 10 mm box centered on ± 5, 40, 10); and (5) PCC (5 × 5 × 10 mm box centered on ± 5, − 60,20). See Supplementary Figure S3 for visual depictions of the ROIs selected for analyses.…”
Section: Fmri Data Analysismentioning
confidence: 99%